Evaluating the Effectiveness of News Literacy Workshops in Strengthening High School Students’ Critical Awareness: Evidence from a Pre–Post Intervention Study in Indonesia - Andini Nur Bahri; Ahmad Yunus Mokoginta Harahap; Arti Damisa; Khairunnisa Hasanah; Rani Afriani (Penerbit Widina, Widina Media Utama, 2025)
The rapid expansion of digital media and social networking platforms has substantially transformed the ways students’ access, consume, and disseminate news, while simultaneously increasing their vulnerability to misinformation and disinformation. This condition underscores the urgency of strengthening news literacy as an essential cognitive and social competence for fostering critical awareness and responsible digital citizenship. This study aims to evaluate the effectiveness of a news literacy workshop in strengthening senior high school students’ perceptions and critical awareness in Indonesia. The study employed a quasi-experimental design using a pre-test and post-test approach involving 91 senior high school students who participated in news literacy workshops conducted at four schools in North Sumatra Province. Data were collected using a news literacy perception questionnaire encompassing conceptual understanding, information verification skills, awareness of media bias, and ethical attitudes toward media use. Data analysis was conducted using descriptive statistics and the nonparametric Wilcoxon Signed Rank Test, complemented by effect size calculations to assess the magnitude of the intervention’s impact. The results indicate a statistically significant increase in students’ mean news literacy perception scores following the workshop, with significance values of p 0.05 and effect sizes ranging from large to very large. The most substantial improvements were observed in indicators related to understanding news structure and news values, recognizing media bias, and applying practical digital information verification skills, including the use of fact-checking tools and reverse image search techniques. Although the normalized gain (N-Gain) was categorized as low, this finding is understandable given the limited duration of the intervention and the complex nature of news literacy, which requires sustained and continuous learning processes. Overall, the findings confirm that news literacy workshops are effective as an initial strategy for strengthening high school students’ critical awareness and news literacy perceptions and have important implications for the development of integrated and sustainable news literacy programs within formal education in Indonesia.